The 'weekend effect' in acute medicine: a protocol for a team-based ethnography of weekend care for medical patients in acute hospital settings. Issue 4 (5th April 2017) - Tarrant, Carolyn; Sutton, Elizabeth; Angell, Emma; Aldridge, Cassie P; Boyal, Amunpreet; Bion, Julian
Abstract : Introduction: It is now well-recognised that patients admitted to hospital on weekends are at higher risk of death than those admitted during weekdays. However, the causes of this 'weekend effect' are poorly understood. Some contend that there is a deficit of medical staff on weekends resulting in poorer quality care, whereas others find that patients admitted to hospital on weekends are sicker and therefore at higher risk of adverse outcomes. Clarifying the causal pathway is clearly important in order to identify effective solutions. In this article we describe an ethnographic approach to evaluating the organisation and delivery of medical care on weekends compared with weekdays, with a specific focus on the role of medical staff as part of National Health Service England's plan to implement 7-day services. Methods and analysis: We will conduct an ethnographic study of 20 acute hospitals in England between April 2016 and March 2018 as part of the High-intensity Specialist-Led Acute Care project (www.hislac.org ). Data will be collected through observations and shadowing, and interviews with staff, in 10 hospitals with higher intensity specialist (consultant) staffing on weekends and 10 with lower intensity specialist staffing. Interviews will be conducted with up to 20 patients sampled from two high-intensity and two low-intensity sites. We will coordinate, compare and contrast observations across our team of ethnographers. Analysis will be both in-depth and cross-cutting, exploring specific features within individual sites and making comparisons between them. We outline how data collection and analysis will be facilitated and organised. Ethics and dissemination: The project has received ethics approval from the South West Wales Research Ethics Committee: Reference 13/WA/0372. Informed consent will be obtained for all interview participants. The findings will be disseminated through peer-reviewed publications in high-quality journals and at national and international conferences.